If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + 4) = 4c + -181 Reorder the terms: 6(4 + c) = 4c + -181 (4 * 6 + c * 6) = 4c + -181 (24 + 6c) = 4c + -181 Reorder the terms: 24 + 6c = -181 + 4c Solving 24 + 6c = -181 + 4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4c' to each side of the equation. 24 + 6c + -4c = -181 + 4c + -4c Combine like terms: 6c + -4c = 2c 24 + 2c = -181 + 4c + -4c Combine like terms: 4c + -4c = 0 24 + 2c = -181 + 0 24 + 2c = -181 Add '-24' to each side of the equation. 24 + -24 + 2c = -181 + -24 Combine like terms: 24 + -24 = 0 0 + 2c = -181 + -24 2c = -181 + -24 Combine like terms: -181 + -24 = -205 2c = -205 Divide each side by '2'. c = -102.5 Simplifying c = -102.5
| 0.1d+0.25(d-7)+0.05(d-7)=8.55 | | 8v^7-18v^2= | | 3v-14=13 | | 2n+25+3n+40=180 | | 24-8x=-2x-10 | | y-2=2(5-7) | | 2m-4=2m | | y^2-14y+6=0 | | 6(5-3u)=-4u-17 | | 9x+-15=10x | | 24-8=-2-10 | | 5x^2+2x=-4 | | 0=(13-0.25x)(12+4x) | | 4x-12+3x=50 | | x^2+2x-4=3x-8 | | 84=4(3m+3) | | (h+12)(h-3)(h)=324 | | 2(3x-6)-3=2(x-5)+11 | | 0.73v+37.9=16v | | -x-3=2x+3 | | 0.75x-4=-10 | | h+10.6=-10.6 | | -1.5(4-n)+2.8=n | | 5x+x=x | | 16+(f+4)= | | x-54=102 | | 3x+18=4x-26 | | 8(c+10)=6(c+4) | | 4x-y=2-2y | | 4x-22=x+5 | | 3x=15/3 | | 21-4x=3(7-8x) |